The effectiveness of promotion strategy towards customer awareness of Netherlands Maritime Institute of Technology/ Faatih Imraan Saypol Anwar - Saypol Anwar, Faatih Imraan (2018)
The higher education institutions play a vital role in the development of a society while higher education websites have many roles to fill. They need to provide information for prospective students, current students. Faculty and alumni, They often need to include reams of information in a way that makes everything easy to explore and it's a great challenge. Looking at another perspective of the industry, education is a really massive business that is actually gaining billions Of dollars in revenue annually, For the purpose of this research, a private institute located in Johor Bahru, Netherlands Maritime Institute of Technology (NWT) is chosen as a subject to generate leads on the best promotion tools to be used to market the institute to prospects. This research will benefit NMIT and also all other institutes located in Malaysia.